Ultrasound-guided percutaneous irrigation of calcific tendinopathy: technical developments - Pagnini, Francesco; D'Amuri, Fabiano Vito; Bevilacqua, Andrea; Sabatino, Vittorio; Russo, Umberto; Zappia, Marcello; Natella, Raffaele; Palumbo, Pierpaolo; Pradella, Silvia; Miele, Vittorio; De Filippo, Massimo (Acta Biomedica Atenei Parmensis, 2019)
Rotator cuff calcific tendinopathy (RCCT) is a common and painful shoulder disease characterised by deposition of calcium into the rotator cuff’s tendond. Different therapeutic options have been proposed, but the ultrasound-guided percutaneous irrigation (US-PICT) is been proved as an effective and safe first-line treatment. It can be performed with a single- of a double-needle tecnique, using warm saline solution to improve the dissolution of the calcific deposit. The procedure is ended with an intrabursal injection of local anaesthetics and slow-release steroids to improve the pain relief and to prevent complications. US-PICT leads to significative improvement in the shoulder funtion and pain relief in the short and long term, with a low complications rate.